The role of melatonin on miRNAs modulation in triple-negative breast cancer cells - Ferreira, Livia C. [UNESP]; Orso, Francesca; Dettori, Daniela; Lacerda, Jessica Z. [UNESP]; Borin, Thaiz F.; Taverna, Daniela; Zuccari, Debora A. P. C. [UNESP] (Public Library Science, 2020)
Melatonin, a hormone secreted by pineal gland, exerts antimetastatic effects by reducing tumor cell proliferation, migration and invasion. MicroRNAs (miRNAs) are small, non-coding RNAs that play a crucial role in regulation of gene expression and biological processes of the cells. Herein, we search for a link between the tumor/metastatic-suppressive actions of melatonin and miRNA expression in triple-negative breast cancer cells. We demonstrated that melatonin exerts its anti-tumor actions by reducing proliferation, migration and c-Myc expression of triple negative breast cancer cells. By using Taqman-based assays, we analyzed the expression levels of a set of miRNAs following melatonin treatment of triple negative breast cancer cells and we identified 17 differentially expressed miRNAs, 6 down-regulated and 11 up-regulated. We focused on the anti-metastatic miR-148b and the oncogenic miR-210 both up-regulated by melatonin treatment and studied the effect of their modulation on melatonin-mediated impairment of tumor progression. Surprisingly, when miR-148b or miR-210 were depleted in triple-negative breast cancer cells, using a specific miR-148b sponge or anti-miR-210, melatonin effects on migration inhibition and c-myc downregulation were still visible suggesting that the increase of miR-148b and miR-210 expression observed following melatonin treatment was not required for the efficacy of melatonin action. Nevertheless, ours results suggest that melatonin exhibit a compound for metastatic trait inhibition, especially in MDA-MB-231 breast cancer cells even if a direct link between modulation of expression of certain proteins or miRNAs and melatonin effects has still to be established.